Best practices in the use of human immunoglobulin preparations for intravenous administration in the treatment of rare neurological diseases - N. M. Tereshchenko; Ya. B. Kushnir; M. P. Abramova; A. A. Gotovchikov; V. S. Krasnov; A. Y. Sokolov; N. A. Totolyan; A. V. Amelin (Бюллетень сибирской медицины)
Aim. To describe best practices in using human normal immunoglobulin in patients with immune-mediated neurological disorders according to the data of one clinical center.Materials and methods. From 2016 to 2021, 20 patients with various autoimmune disorders of the peripheral and central nervous system were treated with human normal immunoglobulin at the Neurology Unit No.1 of Pavlov First Saint Petersburg State Medical University. Treatment efficacy was assessed by changes in the neurological examination data according to specialized scales for specific diseases or clinical manifestations (INCAT, QMGS, MoCA, EDSS). Safety of the therapy was assessed considering the instructions to the drug.Results. In the vast majority of patients, treatment allowed to stabilize the course of the disease or was accompanied by pronounced regression.Conclusion. The considered clinical cases of the use of human normal immunoglobulin preparations demonstrate the possibility of their use in the treatment of a number of autoimmune neurological diseases for unregistered indications.